Anapanasati Practicing Method - Khajonsuwan, Phramaha Veerachai (Journal of Dhamma for Life, 2023)
Anapanasati is a method of meditation that is very important in Buddhism because it is a meditation that can be practiced anywhere and anytime. Even the Lord Buddha attained enlightenment by this method. It also helps the mind to relax. Stress brings peace and comfort and is the only meditation emotion that can be practiced concurrently between Samatha and Vipassana. Anapanasati is, in fact, a tool for the realization of the four foundations of mindfulness, which leads to the full cycle of the seven enlightenment and finally enlightenment and liberation. All of this can happen in a single breath under the condition that it must be practiced correctly. which the Buddha said that “Anapanasati that a monk has developed and done much has great fruit and great merit. A bhikkhu who has developed Anapanasati If you do a lot; you will be able to complete the four foundations of mindfulness. A bhikkhu who has cultivated the four foundations of mindfulness, and has made much of it, can complete the seven enlightenment factors. A bhikkhu who has cultivated the seven enlightenment factors and has made much of them can perfect his knowledge and liberation". Therefore, the development of Anapanasati is important and is a method that is easy to practice and has quick results suitable for people of all ages, whoever has developed and done a lot. It would have a lot of effect and a lot of merit.